Market power and intermediation efficiency in Kenya: Blind spots and empirical clarity - Jared Osoro; Kiplangat Josea (Kenya Bankers Association (KBA), 2020)
This paper seeks to examine the nexus between market power and intermediation efficiency in the Kenyan banking system. Using bank-specific, annual balance sheet and profit and loss data for the period 2003-2018, we construct three measures of efficiency; overall efficiency, allocative efficiency and cost efficiency, deploying the nonparametric Data Envelopment Analysis (DEA) approach with a variable return to scale input minimization orientation. Consequently, we estimate a panel Tobit regression with random effects estimator, to establish the nexus between intermediation efficiency and market concentration as represented by the Herfindahl-Hirschman Index (HHI). At the industry level, market concentration has a significant positive influence across all measures of efficiency implying that economies of scale play into the cost and technical efficiency and consequently allocative efficiency. Considering the heterogeneous nature of the industry's clusters, concentration positively influences allocation efficiency amongst big banks and cost efficiency and overall efficiency amongst small banks. Our inference is that economies of scale underpin allocation efficiency amongst big banks. Further, without the benefit of economies of scale manifested amongst big banks in the influence of cost efficiency on the return on assets (ROA), the middle-sized and small banks have seen their ROA influenced by efficiency across all the three measures. Therefore, the determination that amongst big banks market concentration is associated with allocation efficiency and not overall or cost efficiency is a pointer to the slack in optimal performance of big banks that can only be bridged if economies of scale result in both cost and overall efficiency being influenced by market structure. Based on these findings any arrangements that could influence the level of market power such as mergers and acquisitions are better assessed on how they relate to intermediation efficiency. The implicit policy of a marked-based adjustment of market power in contrast with consolidation activism not hinged on intermediation efficiency is justifiable.
Keywords: 330; Marktmacht; Vermittlungstätigkeit; Effizienz; Bank; Kenia